Local banks, credit supply, and house prices - Blickle, Kristian (Journal of Financial Economics, 2022)
I study the effects of an increase in the supply of local mortgage credit on house prices by exploiting a natural experiment from Switzerland. In 2008, retail customers migrate deposits from universal banks that are suffering overseas losses to homogeneous and narrowly-local mortgage banks. Using the distance between the two types of banks as an instrument for deposit growth, I show that local mortgage banks increase mortgage lending, which correlates with subsequent house price growth in their markets. My results highlight that bank specialization plays an important role in the allocation of capital.